THE EFFICACY OF CREATIVE DRAMA FOR HIGHLY GIFTED STUDENTS TO IMPROVE THEIR SOCIAL SKILLS - Derya ÇİÇEK; Berrin BAYDIK,Ayşe OKVURAN (International Journal of Eurasia Social Sciences, 2017)
This research was conducted to observe the efficacy of creative drama to improve the social skills of gifted students. To gather the data for the study, which was designed in a pre-testing and post-testing control group experimental patterns, Social Assessment Scale Teacher Form (7-12 age) was used, which was improved and tested in terms of reliability and validity by Akçamete and Avcıoğlu. Twelve of 24 students (11-12 age) attending 5th and 6th grades from Yasemin Karakaya Art & Science Center in Yenimahalle, Ankara took part in the experiment group, and 12 of them took part in the control group. Students in the experiment group were engaged in creative drama sessions designed according to the social skills acquisition expected from 7-12 age groups for seven weeks. In order to determine the differences between the pre-test scores of the groups, Mann Whitney U Test was used. The differences between the post-test scores of the groups were also calculated by using the Mann Whitney U Test. The Wilcoxon Signed Rank Test for Paired Samples was used to observe the variations in the scores within the groups. As a result, the findings indicated that social skills acquisition through creative drama was effective for students in gaining basic social skills, skills for initiating and maintaining a relationship, emotional skills, skills for executing a task with a group, conducting chores with a group, speaking skills and interaction skills.